The development of language - Gleason, Jean Berko; Ratner, Nan Bernstein (San Diego, CA : Plural Publishing, Inc., 2024)
'Our book presents language development in an unbiased way; it includes all the major theoretical approaches and evidence that supports each. In addition, we show the real-world applications and relevance of findings in typical language development for children who experience difficulty in learning some aspects of language and communication'--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 30, 2023).
OCLC control number change
Keywords: Language acquisition; Psycholinguistics; Sociolinguistics; Language Development; Psycholinguistics; Langage -- Acquisition; Psycholinguistique; Sociolinguistique; psycholinguistics; sociolinguistics; Language acquisition; Psycholinguistics; Sociolinguistics; Essays; Essays